2023
DOI: 10.3390/nano13101589
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Frictional Properties of Ultrahard AlMgB14 Thin Coatings

Abstract: This paper presents the results of studies on AlMgB14-based ceramic coatings deposited on WC-Co hard alloy substrates using RF plasma sputtering. The aim of this work is to study the structure, phase composition, and mechanical properties of AlMgB14-based coatings depending on the sputtering mode. According to the results of the microstructural study, the bias voltage applied to the substrate during the sputtering process significantly contributed to the formation of the coating morphology. Based on the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The sliding properties were even improved, which was reflected in the drop in the COF to a value of 0.15. The properties of the PVD coatings obtained in this study are comparable to those of similar materials reported in the literature [28].…”
Section: Spectr-3supporting
confidence: 86%
“…The sliding properties were even improved, which was reflected in the drop in the COF to a value of 0.15. The properties of the PVD coatings obtained in this study are comparable to those of similar materials reported in the literature [28].…”
Section: Spectr-3supporting
confidence: 86%
“…The most recent advances and new results include the following: hard and lubricant BAM films produced by DC magnetron sputtering of three elemental targets (B, Mg, Al) [16], employing the process of RF plasma sputtering of AlMgB 14 powder targets [17], AlMgB 14 /TiB 2 composite ceramic brazed onto 304 stainless steel using a commercial Ag-CuTi eutectic foil [18], examination of BAM-coated twist drill wear, the evolution of cuttingedge geometry in drilling experiments with carbon-fiber-reinforced plastic (CFRP) laminate [19] and the novel application of BAM-based ceramic coatings onto the blade edges of razor blades [20] and onto the surfaces of rolling elements in bearing assemblies [21]. Especially noteworthy is the deep nanostructural characterization of the mechanical-tribological behavior and the analysis of the wear rate of nanocomposite TiSiCN coatings deposited on high-Co-based high-speed steel (ASSAB 17) burins [22].…”
Section: Introductionmentioning
confidence: 99%